Billie Eilish’s “Wildflower”: A Study of Lexical Meaning and Metaphor - Suci H N, Chanty; Nurhapitudin, Irman; Huznatul A, Fourus (Journal of English Language and Education, 2025)
Understanding lexical meaning is essential in analyzing song lyrics, and metaphors often enrich that meaning. Although research such as Suprihatin (2019) has explored lexical and contextual meaning in song lyrics, and Ngailo, Suastini, and Pratiwi (2020) have analyzed figurative language in Billie Eilish’s songs, these studies do not specifically discuss how metaphors influence and expand lexical meaning to create emotional depth. Darmawan, Sanditari, and Fauziyah (2024) also focus on semantic meaning in Olivia Rodrigo’s songs, and Salsabila (2022) examines conceptual and associative meaning in Tulus lyrics, but does not explore the relationship between lexical meaning and metaphor. This research aims to fill this gap by investigating how metaphor influences lexical meaning in Billie Eilish’s “Wildflower”. Using a qualitative descriptive method with a semantic approach, this research analyzes the lexical meaning in song lyrics and identifies how metaphors expand the meaning of words. The findings suggest that Eilish uses metaphors to provide additional layers of meaning to her word choices, enriching themes of fragility, growth, and hidden beauty. In conclusion, the strategic use of metaphor enhances the lexical meaning of “Wildflowers”, which contributes to the emotional and artistic impact of the song.